2015
DOI: 10.1111/jvh.12490
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of HBV DNA in immunized children born to HBsAg‐positive mothers, years after being diagnosed with occult HBV infection

Abstract: In a previous study, we observed immunoprophylaxis failure due to occult hepatitis B virus (HBV) infection (OBI) despite the presence of adequate levels of anti-HBs in 21 (28%) of 75 children born to HBsAg-positive mothers. The aim of the study was to explore the maintenance of this cryptic condition in this population. Of 21 OBI-positive children, 17 were enrolled. HBV serological profiles were determined by enzyme-linked immunosorbent assay. Highly sensitive real-time and standard PCR followed by direct sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…Therefore, it might have been necessary to maintain the anti‐HBs titers over certain levels. Sadeghi et al . reported that all 17 children diagnosed with OBI after immunoprophylaxis had ultimately cleared the virus before the age of 7 years.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it might have been necessary to maintain the anti‐HBs titers over certain levels. Sadeghi et al . reported that all 17 children diagnosed with OBI after immunoprophylaxis had ultimately cleared the virus before the age of 7 years.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our findings, the study by Sadeghi et al discovered that HBV DNA disappeared in 94% (16/17) of the OBI-positive children 36 months after the initial sampling. HBV DNA was also undetectable in the still OBI-positive child eighteen months later [12]. They therefore claimed the clearance of HBV in those children.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, 50.0% to 100.0% of the OBI-positive infants of HBsAg-positive mothers demonstrated negativity for anti-HBc [36,12]. It seems to deviate from the consensus that anti-HBc is the lifelong marker of past exposure to or present infection with HBV [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations